Management of Sciatic Nerve Defects: Lessons Learned and Proposal for a New Strategy. Issue 5 (May 2020) - Mathieu, Laurent; Addas, Bassam M. J.; Irimura, Sanae C.; Oberlin, Christophe; Belkheyar, Zoubir
Abstract : Abstract: Management of sciatic nerve injuries can be difficult for surgeons without a special interest in nerve surgery as they would only treat a handful of such cases for many years. Sciatic nerve defects pose the greatest repair challenges, with nerve grafting producing mixed results because of the large size of the nerve in both diameter and length. This article first presents the peculiarities of sciatic nerve defects management, based on the authors experience and a literature review. Various issues are dealt with: When to operate depending on the injury mechanism? What are the results of nerve autografting and allografting? On which component should the repair focus in very large defects? Subsequently, alternatives to conventional nerve grafting are proposed. The authors stress the usefulness of direct nerve suture with knee flexion at 90 degrees, which permits bridging of gaps as much as 8 cm in length. For larger defects, other procedures should be considered: long vascularized nerve grafting in complete lesions, short grafting with knee flexed, or tendon transfers in partial lesions.